A New Version of Time-Pencil Surfaces Around Biharmonic Particles and Its Lorentz Transformations in Heisenberg Spacetime - Korpinar, Talat; Turhan, Essin (Springer/Plenum Publishers, 2014)
In this work, we obtain the new parametric representation for a pencil surface in Heisenberg spacetime . We give a geometrical description of time-pencil surfaces around timelike biharmonic particle in . Moreover, we obtain Lorentz transformations this particles. Additionally, we illustrate some pictures corresponding to different cases for second torsionless.
Keywords: Energy; Bienergy; Heisenberg group; Lorentz transformations; Time-pencil surface; Biharmonic Particle